Assessing the degradation of ochratoxin a using a bioassay : the case of contaminated winery wastewater - Nogueira, R. (2006)
In vineyards the presence of certain fungi may lead to the production of the mycotoxin ochratoxin A (OTA) and subsequent contamination of grapes and wine. Furthermore, winery wastewaters contaminated with OTA may represent an environmental hazard. Therefore it is imperative to assess the fate of this mycotoxin in conventional wastewater treatment systems. The aim of the present work in this context is to assess the biological degradation of OTA. Experimental work was carried out in batch experiments with initial OTA to biomass concentration ratios (S0/X0) of 1.4 μg mg-1, 7.4 μg mg-1 and 11.9 μg mg-1. The assays were inoculated with activated sludge biomass unadapted to the substance under examination. The proposed bioassay demonstrates that OTA concentrations up to 100 μg L-1 can be degraded by microbial activity in activated sludge.